PDTM-31. DRUG SCREENING LINKED TO MOLECULAR PROFILING IDENTIFIES NOVEL DEPENDENCIES IN PATIENT-DERIVED PRIMARY CULTURES OF PAEDIATRIC HIGH GRADE GLIOMA AND DIPG. (5th November 2018) - Mackay, Alan; Carvalho, Diana; Molinari, Valeria; Pemberton, Helen; Temelso, Sara; Burford, Anna; Clarke, Matthew; Fofana, Mariama; Boult, Jessica; Izquierdo, Elisa; Taylor, Katy; Bjerke, Lynn; et al.
Abstract: Paediatric high grade glioma and diffuse midline glioma (including DIPG) are comprised of multiple biological and clinical subgroups, the majority of which urgently require novel therapies. Patient-derived in vitro primary cell cultures represent potentially useful tools for mechanistic and preclinical investigation based upon their retention of key features of tumour subgroups under experimental conditions amenable to high-throughput approaches. We established 21 novel primary cultures derived from patients in London, Dublin and Rome, and together with cultures shared from Barcelona, Brisbane and Stanford we assembled a panel of 42 models under 2D (laminin matrix) and/or 3D (neurospheres) conditions, fully credentialed by phenotypic and molecular comparison to the original tumour sample (methylation BeadArray, panel/exome sequencing, RNAseq). Screening against a panel of 400 approved chemotherapeutics and small molecules, we identified specific dependencies associated with tumour subgroups and/or specific molecular markers. This allowed for functional annotation of distinct variants in human tumours, for example cells with sensitizing (HSJD-GBM-001, PDGFRA _A385ins; HSJD-DIPG-008, PDGFRA _D846N) or resistance (HSJD-GBM-002, PDGFRA _D842Y) mutations to a range of PDGFRA inhibitors. We found individual models showing profound sensitivity to distinct kinase inhibitors based upon cell-specific mechanisms of activation, such as QCTB-R006 to multiple FGFR-targeted drugs, and HSJD-DIPG-012 to those directed against EGFR. Subclasses with functionally relevant pathway-based dependencies included sensitivity of DIPGs with PPM1D mutation (HSJD-DIPG-008, HSJD-DIPG-014) to PARP and MDM2 inhibitors, and MAPK-dysregulated PXA-like cultures (ICR-CXJ-008, ICR-CXJ015) differentially responsive to inhibitors of upstream signalling via PKC and CK2. Of note, all cultures were insensitive to temozolomide. In total, 85% cells were found to have at least one drug screening hit in short term assays linked to the underlying biology of the patient's tumour, providing a rational approach for individualised clinical translation.